Changing images of favorite schools after the student admission system reform in Indonesia - Janu Arlinwibowo; Sri Fajar Martono; Ikhya Ulumudin; Hermanto Waruwu; Yufridawati Yufridawati; Yunita Murdiyaningrum; Gupita Nadindra Fatima; Benjamin Leong Tack Khang (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2024)
The study aims to unearth public perceptions of the label of favorite schools after the implementation of student admission reform in Indonesia, namely the zoning system, and to explore the underlying causes. Adopting a qualitative method with a phenomenological approach, this study involved participants from nine provincial education services, nine regency education services, 72 teachers, and 72 parents. Data collected through in-depth interviews and focus groups reveal three distinctive perceptions of favorite schools. The first view posits that after the implementation of the zoning system, the quality among schools is relatively similar, indicating that the new policy is effective in reducing educational disparity. The second sees that some favorite schools persist, but there is a narrowing educational disparity among schools. The third view, the majority, maintains the belief of the importance of favorite schools and maintains the idea that sending their children to these schools is important to secure a better future. Erasing the label of favorite schools is not an easy endeavor since these schools have created long-lasting positive images in the public landscape. The result of the study will add to the discussion of the impact of the new applied school zone system on public perception of favorite schools and inform policymakers regarding the impact of educational policy enacted.